Correlations between low thyroid function and incidence of atrial fibrillation in hypertrophic obstructive cardiomyopathy. Issue 1 (March 2020) - Liu, Li-Min; Shen, Li-Shui; Liu, Shang-Yu; Tu, Bin; Li, Guo-Liang; Hu, Feng; Hu, Zhi-Cheng; Wu, Ling-Min; Fan, Xiao-Han; Zheng, Li-Hui; Ding, Li-Gang; Yao, Yan
Abstract: Background: Atrial fibrillation (AF) is the most common arrhythmia in patients with hypertrophic obstructive cardiomyopathy (HOCM). Data regarding the correlations of thyroid dysfunction and the incidence of AF in HOCM are quite limited. This study aimed to reveal the correlations between different thyroid status and the corresponding incidence of AF in a large HOCM cohort. Methods: A total of 806 HOCM patients with complete information on thyroid function tests and comprehensive cardiac evaluations were recruited. The participants were divided into the AF group (n = 159) and non-AF group (n = 647) according to established medical history and results of Holter monitoring. The thyroid status of the study population and the corresponding incidence of AF were assessed and analyzed. Results: Hypothyroidism accounted for the greatest proportion of thyroid dysfunction in HOCM patients. The incidence of AF significantly increased in individuals with both overt ( P = 0.022) and subclinical ( P = 0.007) hypothyroidism. Compared with participants in the non-AF group, those with positive AF episodes presented with lower free triiodothyronine (FT3) (2.86 ± 0.52 pg/mL vs. 3.01 ± 0.42 pg/mL, P = 0.001), higher free thyroxine (FT4) (1.24 ± 0.25 ng/dL vs. 1.15 ± 0.16 ng/dL, P < 0.001), and remarkably increased levels of thyrotropin (TSH) (12.6% vs. 5.3%, P = 0.001). Multivariable analyses demonstrated that the concentrations of FT3 (odds ratio [OR] = 0.470, 95% confidence interval [CI]: 0.272–0.813, P = 0.007) and FT4 (OR = 17.992, 95% CI: 5.750–56.296, P < 0.001), as well as TSH levels above normal ranges (OR = 2.276, 95% CI: 1.113–4.652, P = 0.024) were independently associated with the occurrence of AF in the large HOCM cohort. Conclusions: This study indicated a strong link between low thyroid function and the presence of AF in HOCM. Hypothyroidism (both overt and subclinical states) seems to be valuable for assessing the incidence of AF in patients with HOCM.